Pineapple Chips Business Efficiency Analysis In Kampar Regency Riau Province Using Data Envelopment Analysis (DEA) Method - Riska Dian Oktari; Lestari Rahayu Waluyati; Any Suryantini (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2016)
Pineapple chips is a processed product made of pineapple produced in Kampar Regency. Efficient pineapple chips processing will produce both an added value and high profit. The purpose of this research was to determine the level of relative efficiency of pineapple chips business in Kampar Regency in Riau Province. The level of efficiency achieved is a reflection of the quality of good performance. This research used Data Envelopment Analysis (DEA) method to measure the level of efficiency. An analysis using Data Envelopment Analysis (DEA) method with Constant Return to Scale (CRS) assumption through input oriented approach was done to understand the levels of the pineapple chips producers relative efficiency. The research result showed that Most of the pineapple chips producers in Kampar Regency had not been efficient in relative terms, in which from the total of 21 pineapple chips producers, 8 producers were efficient (38,10%) and 13 producers had not been efficient (61,90%). The efficient producers should be a reference for inefficient producer in using inputs. By referring to the efficient producers, it is expected that the inefficient producers could use the input optimally so that the processing pineapple chips business could reach an efficient condition.